Assessment of analgesic and neuropharmacological activity of leaves of Bixa orellana (Family: Bixaceae) - Aktary, Nahida; Sultana, Sharmin; Hossain, M. Lokman (International Journal of Scientific Reports, 2019)
Background: Bixa orellana Linn, (Family: Bixaceae) commonly known as “Lipstick tree” have been extensively used traditional medicine in India and others part of the world to cure laxative, cardiotonic, hypotensive, expectorant, antibiotic, antipyretic, aphrodisaic etc. It has been found that B. orellana contains different phytochemical groups such as phenolic compounds, glycosides, tannins, steroids, alkaloids, saponins. The project work has been designed to investigate the phytochemical nature (group determination of plant constituents), analgesic and neuropharmacological activity of B. orellana leaves extract. Methods: Analgesic activity of B. orellana was determined by acetic acid induced writhing, hot plate, tail immersion and paw tickling test/formalin induced nociceptor test. Open field, hole cross, tail suspension and light/dark box test were employed for the assessment of neuropharmacological activity of B. orellana. Results: Phytochemical screening revealed the presence of reducing sugar, alkaloids, glycosides, gum, terpenoids, tannins, steroids and flavonoids. In analgesic activity test, the sample showed significant analgesic activity. The dose-dependent neuropharmacological activity is shown in neuropharmacological activity test. Conclusions: Our exploration suggests that B. orellana contains bioactive compounds and it should be studied further for isolation and purification of such novel compounds.